Adsorption–Desorption Behaviour of Imidacloprid, Thiamethoxam, and Clothianidin in Different Agricultural Soils - Gabriela Briceño; Graciela Palma; Heidi Schalchli; Paola Durán; Cesar Llafquén; Andrés Huenchupán; Carlos Rodríguez-Rodríguez; María Cristina Diez (Agriculture, 2025)
This study evaluated the adsorption and desorption of imidacloprid (IMI), thiamethoxam (THM) and clothianidin (CLO) in an andisol (Freire soil) and an inceptisol (Chufquén soil) from southern Chile with different organic matter and clay contents. The soils had a slightly acidic pH and clay and clay-loam textures. The tests were carried out at 20 °C with CaCl2 0.01 M as the electrolyte. Kinetic experiments were performed and isotherms were fitted to the pseudo-second-order, Elovich, Weber–Morris, Freundlich and Langmuir models. The kinetics were best described by the pseudo-second-order model (R2 > 0.99), indicating chemisorption; the rate was the highest for THM, although IMI and CLO achieved the highest retention capacities. The Chufquén samples, with lower organic matter but 52% clay, exhibited the highest Kf and qm of up to 12.4 and 270 mg kg−1, respectively, while the Kd (2.3–6.9 L kg−1) and Koc (24–167 L kg−1) coefficients revealed a moderate leaching risk. THM was the most mobile compound due to its high solubility. Desorption was partially irreversible (H = 0.48–1.48), indicating persistence in soil. FTIR analysis confirmed the interaction with O-Al-O/O-O-Si-O groups without alterations in the mineral structure. In the soils examined in this study, the clay fraction and variable-charge minerals, rather than organic matter, were more closely associated with the adsorption behaviour of these NNIs.